2005
DOI: 10.1142/s0218396x05002906
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Curvilinear Simulations of Flows Around Non-Cartesian Bodies

Abstract: The current work describes the application of high-order numerical techniques to single or multiple overset curvilinear body-fitted grids, demonstrating the feasibility of direct computations of noise radiated by flows around complex non-Cartesian bodies. Flows of both physical and industrial interest can be investigated with this approach. We first rapidly describe the numerical techniques implemented in our curvilinear simulations. The explicit high-order differencing and filtering schemes are presented, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Characteristics regarding dispersion and dissipation for the spatial differencing schemes, filters, and the time-integration scheme can be found in previous papers [2,20]. This solver has been validated on reference flow configurations and on a demanding multibody acoustic scattering test case, yielding results in good agreement with experimental and analytical data [12].…”
Section: Numerical Aspectsmentioning
confidence: 88%
See 2 more Smart Citations
“…Characteristics regarding dispersion and dissipation for the spatial differencing schemes, filters, and the time-integration scheme can be found in previous papers [2,20]. This solver has been validated on reference flow configurations and on a demanding multibody acoustic scattering test case, yielding results in good agreement with experimental and analytical data [12].…”
Section: Numerical Aspectsmentioning
confidence: 88%
“…More recently, work on high-accuracy computations around curved geometries has shown that high-precision methods are not restricted to simulations around Cartesian geometries [9][10][11][12]. Cylinders and airfoils have so far been the most-studied curved geometries, due to the large amount of experimental data available and the fundamental academic interest that they present.…”
Section: Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to control this in aero-acoustics simulations, high-order filters which remove grid-to-grid oscillation, can be employed. For instance, to remove π-modes, the velocity field v may be filtered every n time steps (with, e.g., n = 5 or n = 1 depending on the computational grid and the case [19]). In case such a filter is conservative, we have for any function f (x) in the domain Ω, and using f to denote the filtered…”
Section: Conservation Propertiesmentioning
confidence: 99%
“…The spatial derivative in Equation (16) are approximated by the spatial scheme in Equation (4) and the time integration is performed with RK4 yielding:…”
Section: Application On Moving Gridsmentioning
confidence: 99%